LANDSCAPE ECOLOGY AND RESILIENCE OF AGROECOLOGICAL YIELDS: A GLOBAL SYNTHESIS ON ECOSYSTEM SERVICE STABILITY AND FOOD SECURITY - Ramos, Paulo Roberto; Santos, Carlos Alberto Batista; Figueiredo Neto, Acácio; Pereira Filho, Antonio; Pereira, Sidclay Cordeiro; Aragão, Carlos Alberto; Santos, Maria Herbênia Lima Cruz; Santos, Emanuel Ernesto Fernandes; Silva, Mateus Lopes da; Tôrres, Ednaldo Ferreira; et al. (Veredas do Direito, 2026)
Agricultural production systems increasingly face ecological instability driven by biodiversity loss, landscape simplification, and climate variability. While a growing body of research has examined the role of ecosystem services in supporting agricultural productivity, most studies have focused on average yield performance rather than the temporal stability of production across heterogeneous landscapes. This gap limits the understanding of how spatial landscape structure influences the resilience of agroecosystems and their capacity to sustain food production under environmental uncertainty. The main objective of this study was to synthesize global evidence on how landscape configuration influences the stability of ecosystem services and the resilience of agroecological yields. Methodologically, this study employed an integrative literature review conducted between November 2025 and February 2026 across major scientific databases. An initial set of 216 records was identified and subjected to systematic screening procedures based on explicit inclusion and exclusion criteria, resulting in a final analytical corpus of 25 studies addressing interactions between landscape structure, biodiversity, and agricultural productivity. The results indicate that landscape heterogeneity, habitat connectivity, and the presence of semi-natural habitats significantly enhance ecosystem service provision, particularly pollination and biological pest control. These ecological processes contribute not only to increased crop productivity but also to greater yield stability across environmental fluctuations. The findings suggest that agricultural resilience is strongly influenced by the ecological structure of landscapes rather than by input-intensive production strategies alone. In conclusion, designing biodiversity-rich agricultural landscapes emerges as a key strategy for stabilizing ecosystem services and strengthening the resilience of food production systems in the context of global environmental change.